(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper introduces a novel modular multi-source multilevel inverter (MSMLI) topology tailored for renewable energy applications. The proposed architecture features a compact basic unit comprising nine switches, three DC voltage sources, and an H-bridge polarity reversal circuit. With equal source magnitudes, this module produces a 7-level output; configuring the sources in a 1:3 ratio extends the output to 15 levels. By connecting multiple units in series, higher voltage levels can be achieved efficiently in both symmetric and asymmetric modes. Crucially, only four switches need to be active per level, minimizing switching losses and improving overall efficiency. Total harmonic distortion (THD) is significantly reduced—from 12.20% in symmetric operation to 5.38% in asymmetric mode—enhancing waveform quality. Generalized mathematical expressions support both level generation control strategies. Comparative evaluation with existing inverter topologies demonstrates advantages in switch count, THD, and total standing voltage (TSV). The theoretical analysis was validated by experimental results obtained from a laboratory-built prototype. The multi-source capability and low hardware complexity make this MSMLI ideal for integration with sustainable applications.